2022
DOI: 10.1177/07334648221144026
|View full text |Cite
|
Sign up to set email alerts
|

“Friend-ish”: Home Care Workers, “Social Labor” and Managing the Boundaries of the Carer Relationship

Abstract: We examine how changes in home care work, with greater emphasis on social support, have led to corresponding changes in the forms of labor performed by home care workers. Drawing on interviews with fifty older adults, we find in addition to physical and emotional labor, workers may be increasingly expected to engage in a form of labor we term “social labor,” in which they actively manage the boundary between the professional services they provide and the personal relationships that may develop. We find example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…Similar to a recent study by Lam and Baxter, 42 we found that HHAs create and maintain boundaries between their professional and personal relationships. A key strategy was compartmentalizing, since participants found that it prevented their emotions from compromising patient care.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to a recent study by Lam and Baxter, 42 we found that HHAs create and maintain boundaries between their professional and personal relationships. A key strategy was compartmentalizing, since participants found that it prevented their emotions from compromising patient care.…”
Section: Discussionsupporting
confidence: 89%